Investigating the Relationship between Professional Ethics and Job Performance of Employees in Selected Educational Hospitals of Yazd in 2021 - Roohollah Askari; Fatemeh Shamsaddin; Arefeh Dehghani Tafti; Hasan Jafari (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: Job performance is the most critical organizational issue determining the survival or dissolution of an organization. Professional ethics are among the major factors promoting job performance. Since professional ethics and job performance contribute greatly to the enhancement of productivity, the present study aimed to assess the relationship between professional ethics and job performance of staff in selected hospitals of Shahid Sadoughi University of Medical Sciences in 2021. Methods: This applied research was conducted based on a descriptive cross-sectional design conducted on 180 employees of selected hospitals in 2022. The subjects were randomly selected and administered the Work Ethic Questionnaire of Gregory, C., Petty, and Job Performance Questionnaire by Patterson. Data were analyzed in SPSS software (version 16) using Kruskal-Wallis and Mann-Whitney tests. Results: The results pointed to a positive and significant relationship between professional ethics and job performance. The correlation coefficients of "interest in work', "perseverance", "healthy relationships", "collective spirit and participation in work" were reported as 0.355, 0.551, 0.483), and 0.386, respectively. Demographic variables (marriage, education, age, and professional experience) showed a significant relationship with professional ethics, and demographic variables (gender, marriage, age, and work experience) were correlated with job performance. Conclusion: As evidenced by the findings of this study, the promotion of ethics can increase employees' job performance. Since job performance directly improves organizational productivity, these two variables deserve assiduous attention.